The six days of destruction : meditations towards hope - Wiesel, Elie, 1928-2016 (Pergamon Press, 1988)
"If you do not take up this text to pray, take it as a book to be studied. Once you have read these stories, they will not leave you, for they are part of human history." (From the Introduction by Albert Friedlander). The Six Days of Destruction is a religious text for use in both Jewish and interfaith services for Yom Ha-Shoah; it also stands on its own as a work of great poignancy. The six stories were written by Nobel Peace Prize Winner, Elie Wiesel, with liturgies by Rabbi Albert Friedlander. The book opens with prefaces by Cardinal Basil Hume, Bishop Richard Harries and Lord Jakobovits, and is illustrated with a collection of drawings by inmates of the Nazi concentration camps, introduced by Elisabeth Maxwell and Roman Halter